Insect migration monitor - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
An automatic monitor of insect migration has been developed by the UK's Natural Resources Institute (NRI). The vertical looking, insect-detecting radar is intended to improve the fore casting of migrant insect pest movement so that control can be...